2 Correlation analysis of bone mineral density and static balance ability in postmenopausal women. (March 2019) - Xu, Lili; Han, Yue; Zhang, Yan hua; Zhang, Xiao ying; Fan, Chun; Huang, Hai tao; Li, Peng; Geng, Zhuang
Abstract : Objective: To assess static balance ability in postmenopausal women and to explore the correlation between bone mineral density and static balance. Methods: From January 2017 to January 2018, 400 postmenopausal and non-menopausal women living in the Qingdao area of Shandong Province were included in the study. Inclusion criteria were: Han nationality, natural menopause years ≥1 year, 50–80 years old, non-smokers, wine drinker. Those with diseases such as diabetes, hyperthyroidism, chronic liver and kidney disease, which cause secondary and idiopathic osteopenia were excluded. (1) Questionnaires were used to collect information on the postmenopausal women such as name, gender, age, family history, osteoporosis-related symptoms (eg, lower back pain, dwarf, hunchback, fracture), related diseases (eg, thyroid disease, gastrointestinal pathology, parathyroid disease, renal insufficiency, diabetes), exercise (exercise mode, time), smoking, drinking, tea or coffee consumption, age at onset of menopause, pregnancy, parity, breastfeeding time, weight, height, blood pressure, blood sugar and other related indicators. (2) Determination of bone mineral density: the T value of the right heel of the examiner was measured using a Sahara clinical ultrasonic bone densitometer manufactured by HOLOGIC, USA. (3) Gait measurement: the Belgian Footscan Balance system was used to measure the ability of the subject to reflect the balance ability when standing still, including total trajectory length (TTW) of the trajectory of the pressure center movement and the elliptical area (EA) of movement in the 95% pressure center. (4) The difference between the non-menopausal group and the postmenopausal group was compared using the t-test of two independent samples. (5) According to the bone mineral density level, the non-menopausal group and the postmenopausal group were divided into three groups. The differences in TTW and EA were analyzed in the different bone density level groups. Further correlation analysis was used to analyze the balance indices and bone mineral density levels in the postmenopausal group. Results: Compared with the non-menopausal group, the post-menopausal group had lower bone mineral density and increased TTW and EA. Conclusion: Postmenopausal women have lower bone mineral density and lower static balance ability. Postmenopausal women's bone mineral density is negatively correlated with TTW and EA (the lower the bone mineral density, the greater the TTW and EA values). Bone density level is an important factor affecting the static balance ability of postmenopausal women.